The Impact of Leadership and Rewards on Project Management Success, Mediated by Employee Perception and Team Cohesion - Shah Mehmood Wagan; Sidra Sidra; Atif Ali Wagan (Journal of Construction Project Management and Innovation, 2025)
The increasing competition in companies necessitates an emphasis on project management to accomplish success. Leaders must possess both technical and social skills, as their management and perception significantly influence decision-making and team cohesion. The usage of diverse leadership rewards, and styles, both non-financial and financial, by project management leaders, nurtures team cohesion, promotes team essence, and motivates necessary project decisions. This study investigates the impacts of directive and supportive leadership, mediated by work team cohesion and non-financial, and financial rewards, on project success. A research model was established based on a literature review, analyzing the relationship between the causes and effects of the research variables. A questionnaire was collected from 237 individuals in project management teams over the last 6 months from the Munich Bavaria region of Germany. From the results obtained, it appears that directive leadership and supportive leadership positively influence the cohesion of work teams. In this work, it was also found that directive leadership has a positive impact on the success of project management for the client and that financial rewards have an opposite effect. It is concluded that organizations must value the importance that adjusted leadership, on the part of the manager, has in team cohesion and that the financial rewards system used by companies is something to take into account when they set out to achieve success. The importance of this research lies in the fact that with its empirical findings, it provides information on how the various types of leadership and reward systems impact team cohesion and project success, which has been a substantial gap in project management literature and is of great symbolic help to the developing organization with the effective leadership and motivational strategies, which can impact the project outcome results.